1994
DOI: 10.1111/j.1469-8137.1994.tb02986.x
|View full text |Cite
|
Sign up to set email alerts
|

Stems of Allium cepa L. contain starch

Abstract: SUMMARYStems oi Allium cepa L. were prepared for histochemical analysis and stained by periodic acid-Schiff reaction and Lugol's iodine for detecting starch grains (amyloplasts). Starch was found in the root cap of the root initials, around the central cylinder vascular tissues of the stem and in the primary thickening meristem during sprouting hut not during dormancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
4
8
0
Order By: Relevance
“…Histological examinations on Helianthus tuberosus showed that low amounts of starch are detectable in the tuber during tuber development and the beginning of sprouting, but not during dormancy (Ernst 1991). A similar result was obtained for onion bulbs (Ernst and Bufler 1994). Fructan, the principal carbohydrate reserve, is found throughout the onion bulb (Darbyshire and Henry 1978), while the occurrence of starch is restricted to the stems (=basal plate).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Histological examinations on Helianthus tuberosus showed that low amounts of starch are detectable in the tuber during tuber development and the beginning of sprouting, but not during dormancy (Ernst 1991). A similar result was obtained for onion bulbs (Ernst and Bufler 1994). Fructan, the principal carbohydrate reserve, is found throughout the onion bulb (Darbyshire and Henry 1978), while the occurrence of starch is restricted to the stems (=basal plate).…”
Section: Introductionsupporting
confidence: 86%
“…Fructan, the principal carbohydrate reserve, is found throughout the onion bulb (Darbyshire and Henry 1978), while the occurrence of starch is restricted to the stems (=basal plate). Starch can be detected in its primary thickening meristem during sprouting but not during dormancy (Ernst and Bufler 1994). These results allow for speculation that the two carbohydrates – fructan and starch – fulfil different roles during specific phenological phases (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, macroscopically visible growth of the dormant structure (sprout leaves), but not mitotic activity (Abdalla and Mann, 1963;Matejko and Dahlhelm, 1991;Pak et al, 1995), absence of starch in the primary thickening meristem (Ernst and Bufler, 1994), or (Miedema, 1994), was the basis for dormancy evaluation. As in young photosynthetic leaves (Heath and Hollies, 1965), the leaf blades of sprout leaves started to elongate long before elongation of the leaf sheath (Figure 1), therefore allowing the collection of sprout leaves of the same size-class at each sampling date during the experimental period (Bufler, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In onion (A. cepa L.) bulbs low-molecular-weight fructans are the principle storage carbohydrate, whereas starch is far less abundant (28,29). In onions the total amount of extractable carbohydrates is FIG.…”
Section: (B) Fructans From a Cepa Lmentioning
confidence: 99%